Integrating Green Banking into Sustainable Development Strategies for Commercial Bank Efficiency - Siswanti, Indra; Riyadh, Hosam Alden; Nawangsari, Lenny Christina; Cahaya, Yohanes Ferry; Putra, Yananto Mihadi (Pandawan, 2026)
Digital banking is rapidly transforming commercial bank operations by improving efficiency, service quality, and sustainability orientation. Banks face increasing pressure to balance financial performance with environmental and social responsibility. In Indonesia, this transformation is closely linked to Green Banking (GB) practices and operational efficiency to support sustainable business performance. This study examines the effect of digital banking on the sustainable business performance of Indonesian commercial banks and investigates the mediating roles of GB and efficiency, as well as the moderating role of foreign ownership. The population includes all KBMI 3 and 4 banks, totaling 13 commercial banks. A saturated sampling technique was used, and the data were analyzed using EViews 12. Digital banking significantly enhances sustainable business performance and promotes GB and efficiency. GB positively affects sustainability and mediates the digital banking sustainability relationship. Efficiency (measured by BOPO) improves sustainability but does not mediate the effect. Foreign ownership does not moderate the relationship. Digital banking contributes to sustainability mainly through strengthening GB rather than efficiency alone. The absence of mediation by efficiency and moderation by foreign ownership represents an important boundary condition and a key contribution of this study.